ANALYSIS OF CUSTOMER PREFERENCE ON THE COWPEA TEMPE - Catur Rini Sulistyaningsih, Agung Setyarini & (Proceeding of International Congress, 2014)
The aim of this research are to analyze the customer preference on cowpea tempe, to know the proportionsubstitusion of cowpea on soybean in making tempe that as a favorite food by costumer, and to know thenutritions of cowpea tempe. The research is done in Laboratory of Food and Nutrition, Agriculture Facultyof Sebelas Maret University. The research steps were in making tempe by using soybean which is substitutedby cowpea with comparison 0: 20: 40: 60: 80: 100. Testing of organoleptic includes: color, texture,aromatic, and taste. Testing of proximate includes: the content of protein, fat, carbohydrate, water, andashes.The method which is used is Non Probability Sampling. The participants who are joined in this researchare untrainner. They are 60 people in Jombor Village, Bendosari, Sukoharjo. The data analyze usesanalysis variant 5% and there is a real difference to continue the Duncan Multiple Range Test (DMRT).The result of this research shows that the customer preference on tempe which is subtituted by cowpeaabout 20% just consist of color and taste eventhough the texture and aromatic the customer preferencestill depends on soybean tempe. Based on organoleptic test, it is gained result that people didnât liketempe with a lot of cowpea substitution. It is because the color is brownish, the texture is not compact,the aromatic is sour and the taste is unpleasant. Cowpea tempe consists of less protein and fat than soybeantempe which has the highest carbohydrate than soybean tempe, and also has water and ashes contentwhich similar with soybean tempe.Keywords: customer preference, tempe, cowpea